PENYELESAIAN KREDIT BERMASALAH PADA PD.BANK PENGKREDITAN RAKYAT DAERAH LAMONGAN TAHUN 2017 - Anggeri Nika Kumalasari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to analyze the problem loans at Bank Daerah Lamongan. The purpose of this study is to determine the factors of increasing non-performing loans, and to know the process of settlement of non-performing loans at Bank Lamongan Regional. This research is qualitative interactive, data collection conducted in this research with interview and documentation. The results of this study can be concluded that the factors that resulted in problem loans that failed aha or failed harvests and ihktikad less good than customers. While the completion is done by Bank of Lamongan through personal approach, rescheduling, and restructuring.